Enhancing Islamic Education: The Role of Madrasah-Based Management in Islamic Boarding Schools - Badrun Badrun (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to analyze the contribution of madrasah-based Islamic education management, focusing on planning, organizing, implementing, supervising, and assessing. The research highlights the potential of effective management practices within madrasahs to enhance the quality of education, particularly in Islamic boarding schools (pesantren). Using a qualitative approach and a case study design, this research seeks to reveal empirical facts objectively and scientifically, supported by strong methodology and theory. Data collection methods include observations, interviews, and documentation, while data analysis follows a systematic process involving data collection, analysis, and conclusion drawing. The findings underscore the significant role of madrasah-based management in improving education quality at Madrasah Aliyah in the Darussalam Bermi Islamic Boarding School. Key contributions include the proactive leadership of boarding school authorities, collaboration with stakeholders, integration of a dual curriculum (government and pesantren-specific), and the resulting high quality of graduates. The collaboration between stakeholders and the dual curriculum system significantly impacts educational outcomes, as evidenced by the alumni's quality. The study indicates that madrasah-based management practices, particularly the dual curriculum, do not present significant issues within pesantren. Instead, these practices positively impact educational quality. Effective management strategies, leadership, and stakeholder collaboration are crucial to this success. The integration of the Ministry of Religion’s curriculum with the boarding school’s specific curriculum demonstrates adaptability and effectiveness. This study provides a foundational understanding of madrasah-based Islamic education management’s contribution to improving educational quality. The successful implementation of a dual curriculum and stakeholder involvement are key factors. These findings offer a framework for further research into the contributions and best practices of madrasah-based management in Islamic education.